Taxonomic adjustments in the systematics of the southern African lacertid lizards (Sauria: Lacertidae) - Edwards, Shelley; Branch, William R.; Vanhooydonck, Bieke; Herrel, Anthony; Measey, G. John; Tolley, Krystal A. (Zootaxa, 2013)
Molecular phylogenetic analyses of southern African lacertid lizards (Eremiadini) using mitochondrial and nuclear markers revealed two examples of generic assignments incompatible with monophyletic clades. Australolacerta Arnold 1989, a genus endemic to South Africa and to which two isolated species have been referred, is paraphyletic at the generic level. In addition, the species Ichnotropis squamulosa Peters 1854 was found to be embedded within the genus Meroles. To resolve the paraphyly in Australolacerta we erect a new genus, Vhembelacerta Edwards, Branch, Herrel, Vanhooydonck, Measey, & Tolley, gen. nov., to accommodate Lacerta rupicola FitzSimons 1933. To maintain a monophyletic Ichnotropis Peters 1854, Ichnotropis squamulosa Peters 1854 is transferred to Meroles Gray 1838, now named Meroles squamulosus comb. nov. Where necessary the genera affected by these actions are re-characterized.